THE PROBLEM OF SOIL DEFLATION IN THE AGROLANDSCAPES OF VOLGOGRAD REGION ARID ZONE - Marina V. Nazarova; Alexander М. Belyakov (Siberian Journal of Life Sciences and Agriculture)
Background. The climate is changing towards aridization and increasing on anthropogenic impact lead, among the other things, for example, a deflation, a loss of soil fertility and a desertification of agricultural landscapes, which negatively gives effect on their environmental sustainability and agricultural productivity.